Hypertensive Disorders of Pregnancy among Mothers of Medically Fragile Infants [38R]. (May 2018) - Stuebe, Alison M.; Tucker, Christine; Bryant, Katherine; McClain, Erin; Ferrari, Renee; Verbiest, Sarah
Abstract : INTRODUCTION: We sought to quantify the prevalence and early postpartum (PP) follow-up for hypertensive disorders of pregnancy among mothers of medically fragile infants (MMFI). METHODS: We conducted a retrospective cohort study of mothers delivering at North Carolina Women's Hospital between 7/1/2014 and 6/30/2016. We defined MMFI as mothers of infants with a NICU length of stay ≥3 days and mothers of well babies (MWB) as mothers of infants not admitted to the NICU. We ascertained hypertensive disorders using blood pressures (BP) measured in routine clinical care between 20 weeks of pregnancy and PP discharge from Electronic Medical Records. Rates of mild and severe hypertension and completion of recommended follow-up among MMFI and MWB were compared with chi square test. RESULTS: Among 6, 851 women who gave birth to one or more liveborn infants, 34.4% met criteria for mild hypertension, and 9.0% for severe hypertension. Hypertension was more common among MMFI; 38.2% met criteria for mild hypertension and 26.1% for severe hypertension. Among women with an indication, MMFI were more likely than MWB to have a PP BP check between discharge and 10 days PP (22.0% vs. 14.2%, p=0.01). MMFI whose infants were still hospitalized at 10 days PP were no more likely than MMFI whose infants had been discharged to have had a PP BP check (23.2 vs 22.8%, p=0.93). CONCLUSION: The prevalence of hypertensive disorders among MMFI is high, and few received indicated PP BP follow-up assessment. Evaluation of maternal health at the infant's bedside may improve follow-up and reduce maternal morbidity.